(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
The historical distance between Hesychius, whose life dates (approx. AD 500) are only a rough estimate, and the Lydian Empire amounts to over a millennium, and a similar distance separates his work from the oldest surviving manuscript at the Marciana Library in Venice. The Hesychian lexicon contains a number of glosses referring to the Lydians which have been particularly badly understood, and therefore have been subject to emendation throughout their reception history. This unpromising situation is slowly improving due to continued work on the Lydian language and surviving inscriptions. The present article addresses a selection of Lydian glosses preserved in the Marciana manuscript.